The Legal Status of Circumstantial Evidence in the Context of Criminal Cases in Indonesia - Hari Wibowo; Dodi Jaya Wardana; Levina Yustitianingtyas; Hasnan Bachtiar (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
In practice, there are several instances of criminal decisions that are not in accordance with the law. In such instances, the judge interprets the law or legal findings based on circumstantial evidence. As a result, the action taken does not achieve the highest degree of justice and legal certainty in a decision. This is because the decision is not based on the minimum requirements of two pieces of evidence that must be met in terms of evidence to impose a sentence. The objective of this research was to analyze the legal status of circumstantial evidence in the context of criminal cases. Our research findings indicate that the philosophy of circumstantial evidence, as it pertains to criminal procedural law, represents a form of evidence that can be considered by judges in relation to the absence of facts that are not directly visible by eyewitnesses. This evidence is intended to provide a comprehensive depiction of the truth of an event, thereby facilitating the acceptance of a reasonable account of events. Establishing circumstantial evidence is distinct from providing instructions, however. To do so, one must obtain clues from facts presented at trial in the form of witness statements, letters and statements of the accused. The ius constituendum application of circumstantial evidence in the process of proving a criminal case is to provide the judge with the authority to utilise circumstantial evidence in the process of proving a crime as an additional legal means of evidence in sentencing. The role of indirect evidence in the imposition of criminal penalties is a doctrine that is confined to be the domain of legal experts.